BIMBINGAN DAN PELATIHAN TENTANG PENTINGNYA KUALITAS PELAYANAN DAN TOKO ONLINE BAGI PENGEMBANGAN USAHA GARMEN “AMAR” DI MALANG - Joko Samboro; Abdullah Helmy; Zubaidi Zubaidi; Tri Wahyu Widodo; Rulirianto Rulirianto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The aim of the Community Service Program is to find problems faced by partner companies and at the same time provide appropriate solutions to achieve sales and knowledge enhancement and the ability of entrepreneurs in the operational field, especially in marketing management. The program partner is Amar garment entrepreneur Mr. Abdul KhodirThe problems faced by Partners are: 1. Don't know about good Service Quality. 2. Non-fulfillment of sales targets because they do not understand selling techniques and still use traditional marketing media.The method used is: observation, to observe the activities carried out by entrepreneurs in making and marketing goods, then interviews, are explored to find problems and solutions to be offered and simulations, to find the most appropriate alternative for marketing goods to be more effective.The solutions offered are: 1. Guidance and Training on Good Service Quality. 2. For marketing aspects: to expand product marketing, there will be training on selling techniques and online marketing training to market their products, so that marketing reach will be wider and sales can be increased.